Evaluation of the potential of dimethyl phthalate degradation in aqueous using sodium percarbonate activated by discharge plasma - Wang, Tiecheng; Jia, Hanzhong; Guo, Xuetao; Xia, Tianjiao; Qu, Guangzhou; Sun, Qiuhong; Yin, Xianqiang (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
[Display omitted] •SPC activated by discharge plasma is used to remove plasticizer from wastewater.•Plasticizer removal efficacy under various experimental conditions is evaluated.•Roles of active species in plasticizer removal are evaluated.•Mineralization process and byproducts formation are explored.•Enhancement mechanisms on plasticizer removal in such a system are discussed. Phthalates, as additives in the plastic production process, were able to enter the water environment, causing huge risks to ecological environment and human health. The potential of phthalates elimination in aqueous using sodium percarbonate (SPC) activated by discharge plasma (marked as “SPC + plasma”) was evaluated, with dimethyl phthalate (DMP) as a model pollutant. Experimental results showed that about 92.1% of DMP was eliminated in the “SPC + plasma” system with the treatment time of 30 min, which was 30.7% higher than that in sole plasma system, and the synergetic intensity for DMP elimination reached up to 127.0; and the energy yield was also raised by 131%. H2O2 and OH radicals formation were promoted but ozone concentration decreased in the “SPC + plasma” system. Appropriate SPC dosage benefited DMP elimination, and the synergetic intensity increased from 2.0 to 127.0 as the SPC dosage increased from 0.06 mmol L−1 to 0.12 mmol L−1. OH radicals, O2·−, 1O2, and CO3·− played crucial roles in DMP elimination, and the roles of O2·− and 1O2 were strengthened in the “SPC + plasma” system. Ultraviolet–visible spectroscopy measurement, total content of organic carbon, atomic force microscopy and three-dimensional fluorescence analysis demonstrated that DMP molecular structure was destroyed during treatment, and some smaller molecular fractions were generated. The main intermediates included phthalic acid monomethyl ester, phthalic acid, o-phthalic anhydride, acetic acid, formic acid, and oxalic acid. The possible enhancement mechanisms for DMP elimination in the “SPC + plasma” system were proposed.